Kajian Kearifan Lokal Dalam Usahatani di Desa Warembungan Kecamatan Pineleng Kabupaten Minahasa - JAMAL . HUSSEIN (Universitas Sam Ratulangi, 2012)
Jamal Hussein. The study of Agricultural Local Wisdom in Warembungan Village, Pineleng Subdistrict, Minahasa Regency. Under guidance of Ventje V. Rantung as chairman, with Oktavianus Porajouw and Martha Sendow as members. The objective of this research is to identify and fully describe the agricultural local wisdom wich is excecuted by farmers community in every agriculture steps at Warembungan Village. This research used primarary and secondary data. The first primary data was obtained from location observe which held by participant observatory, it means researcher immediately step in to the location where agricultural local wisdom was held by farmers community in Warembungan Village and see the excecution directly. The other primary data was obtained from in-depth interviews with key informant in this research, which is the local tradition leader, also known as tonaas. The interviews also done with the Warembungan Village’s farmers community by focus group discussion (FGD). As for secondary data, which is used for fulfilled the information about village’s profile was obtained from Warembungan Village’s government/administration office. The method of data analysis is qualitative study and presented in narrative descriptive form. The results of this research concluded that are 10 local wisdoms form that still excecuted by Warembungan Village’s farmers community. These local wisdoms were tumalinga, which held before start the agriculture works, the technic of rumokrok, rumuru and tumutung, which held in field preparation stage, the technic of kumeror, which held in cultivation stage, the tradition of mauru, which held as plants protection attempt, the habit to splash rice water and kai roya water to cure the infected plants, the habit to hanging salt in some of the top of clove trees as the attempt,to protected the plants from pests, the habit to combine cultivation of clove trees, banana trees, and rice leaves in 1 location, and also the tradition of ulu hasil, which is always held at the beginning of harvest season. These local wisdom are the knowledge which contained of goodness and wise values that will give benefits to farmers who excecuted it. The recent existed local wisdom are proven has some advantages because it was formed by a long experience of earlier farmers who struggle to formulate the agriculture knowledge system which can maximize farming output. These local wisdom also become the cultural legacy that have to get everlasted by the community.